Contamination of basalt through silicic melts: The first chaotic dynamics experiments with Paraná-Etendeka starting materials - Caio M. Vicentini; Cristina P. de Campos; Werner Ertel-Ingrisch; Leila S. Marques; Donald B. Dingwell; Diego Perugini (Chemical Geology, 2023)

Rifting and recharge as triggers of the mixed basalt–rhyolite Halarauður ignimbrite eruption (Krafla, Iceland) - Shane M. Rooyakkers; John Stix; Kim Berlo; Daniele Morgavi; Maurizio Petrelli; Monika K. Rusiecka; Simon J. Barker; Bruce L. A. Charlier; David A. Neave; Francesco P. Vetere; Diego Perugini (Contributions to Mineralogy and Petrology, 2022)

The San Gregorio Magno lacustrine basin (Campania, southern Italy): improved characterization of the tephrostratigraphic markers based on trace elements and isotopic data - P. Petrosino; I. Arienzo; F. C. Mazzeo; J. Natale; M. Petrelli; A. Milia; D. Perugini; M. D′Antonio (Journal of Quaternary Science, 2019)
Central–southern Italy is one of the most suitable areas in the world for tephrostratigraphic studies, owing to the numerous volcanic sources with explosive activity during the Pleistocene. This work presents a systematic investigation of the chemical (trace elements) and isotopic (Sr and Nd) compositions of the main tephra markers within lacustrine sediments of the San Gregorio Magno Basin (Campania, southern Italy). This study: (i) provides full geochemical (trace elements and isotopes) characterization of eight significant Upper Pleistocene marker layers (X‐6, X‐5, C‐22, MEGT/Y‐7, CI/Y‐5, C‐10, Y‐3, NYT/C2) widely dispersed over the Mediterranean area; (ii) proposes a new tephra marker for Marine Isotope Stage 7, dated to 240 ka; and (iii) refines the correlations of tephra levels belonging to the investigated sequence. This study highlights that in most cases the Nd isotope composition of the glass and Sr isotope composition of the coexisting minerals are more reliable than 87 Sr/ 86 Sr of the glass, and hence is more helpful as a further tool for tephrostratigraphic correlations, as recently proposed in the literature. Moreover, this study is a first step towards the construction of a complete geochemical database for future tephra investigations in the Mediterranean area. Copyright © 2019 John Wiley & Sons, Ltd.

Characterization of recombinant dihydrodipicolinate synthase from the bread wheat Triticum aestivum - Ruchi Gupta; Campbell J. Hogan; Matthew A. Perugini; Tatiana P. Soares da Costa (Planta, 2018)

Molecular evolution of an oligomeric biocatalyst functioning in lysine biosynthesis - Tatiana P. Soares da Costa; Belinda M. Abbott; Anthony R. Gendall; Santosh Panjikar; Matthew A. Perugini (Biophysical Reviews, 2018)

Phosphorus zoning as a recorder of crystal growth kinetics: application to second-generation olivine in mantle xenoliths from the Cima Volcanic Field - I. Baziotis; P. D. Asimow; T. Ntaflos; J. W. Boyce; F. M. McCubbin; A. Koroneos; D. Perugini; S. Flude; M. Storey; Y. S. Liu; S. Klemme; J. Berndt (Contributions to Mineralogy and Petrology, 2017)

Experimental constraints on the origin of pahoehoe “cicirara” lavas at Mt. Etna Volcano (Sicily, Italy) - F. Vetere; S. Mollo; P. P. Giacomoni; G. Iezzi; M. Coltorti; C. Ferlito; F. Holtz; D. Perugini; P. Scarlato (Bulletin of Volcanology, 2015)

Time evolution of chemical exchanges during mixing of rhyolitic and basaltic melts - Daniele Morgavi; Diego Perugini; Cristina P. De Campos; Werner Ertel-Ingrisch; Donald B. Dingwell (Contributions to Mineralogy and Petrology, 2013)

Enhancement of magma mixing efficiency by chaotic dynamics: an experimental study - Cristina P. De Campos; Diego Perugini; Werner Ertel-Ingrisch; Donald B. Dingwell; Giampiero Poli (Contributions to Mineralogy and Petrology, 2011)

Time-scales of recent Phlegrean Fields eruptions inferred from the application of a ‘diffusive fractionation’ model of trace elements - Diego Perugini; Giampiero Poli; Maurizio Petrelli; Cristina P. De Campos; D. B. Dingwell (Bulletin of Volcanology, 2010)

Monitoring of levels of polycyclic aromatic hydrocarbons in bees caught from beekeeping: remark 1 - M. Amorena; P. Visciano; A. Giacomelli; E. Marinelli; A. G. Sabatini; P. Medrzycki; L. Persano Oddo; F. M. De Pace; P. Belligoli; G. Di Serafino; S. Saccares; G. Formato; et al. (Veterinary Research Communications, 2009)

γ-Irradiation of PEGd,lPLA and PEG-PLGA Multiblock Copolymers: I. Effect of Irradiation Doses - R. Dorati; C. Colonna; M. Serra; I. Genta; T. Modena; F. Pavanetto; P. Perugini; B. Conti (AAPS PharmSciTech, 2008)

Pm37, a new broadly effective powdery mildew resistance gene from Triticum timopheevii - L. D. Perugini; J. P. Murphy; D. Marshall; G. Brown-Guedira (Theoretical and Applied Genetics, 2008)

5-Methyl-Pyrrolidinone Chitosan Films as Carriers for Buccal Administration of Proteins - C Colonna; I Genta; P Perugini; F Pavanetto; T Modena; M Valli; C Muzzarelli; B Conti (AAPS PharmSciTech, 2006)